2001
DOI: 10.1016/s0169-328x(01)00044-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultured olfactory ensheathing cells express nerve growth factor, brain-derived neurotrophic factor, glia cell line-derived neurotrophic factor and their receptors

Abstract: In the primary olfactory pathway axons of olfactory neurons (ONs) are accompanied by ensheathing cells (ECs) as the fibres course towards the olfactory bulb. Ensheathing cells are thought to play an important role in promoting and guiding olfactory axons to their appropriate target. In recent years, studies have shown that transplants of ECs into lesions in the central nervous system (CNS) are able to stimulate the growth ofaxons and in some cases restore functional connections. In an attempt to identify a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
215
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(224 citation statements)
references
References 62 publications
8
215
0
1
Order By: Relevance
“…A subsequent study (Kafitz and Greer, 1999) demonstrated that olfactory receptor cell extension in culture was facilitated by exposure to media conditioned by ECs, indicating that the neurite growthpromoting properties of ECs were, at least in part, mediated by diffusible factors. Data supporting this idea was reported earlier this year, when cultured ECs were found to express nerve growth factor, brain-derived neurotrophic factor, and glial cell linederived neurotrophic factor (Woodhall et al, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…A subsequent study (Kafitz and Greer, 1999) demonstrated that olfactory receptor cell extension in culture was facilitated by exposure to media conditioned by ECs, indicating that the neurite growthpromoting properties of ECs were, at least in part, mediated by diffusible factors. Data supporting this idea was reported earlier this year, when cultured ECs were found to express nerve growth factor, brain-derived neurotrophic factor, and glial cell linederived neurotrophic factor (Woodhall et al, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Rodent and human OECs generate Schwann-cell-like myelin and improve conduction properties when transplanted to areas of demyelination in the brain or spinal cord [227,233,[235][236][237][238][239][240]. OECs also have the capacity to promote axonal growth [241] and to secrete neurotrophic molecules [242,243]. Thus, the relative availability of these cells, their apparent myelinating properties and their trophic effect on axonal growth make them another promising candidate for autologous therapeutic transplantation.…”
Section: Olfactory Nerve Ensheathing Cellsmentioning
confidence: 99%
“…35 Possible mechanisms of rapid neurological changes Trophic effects due to factors released from the transplanted cells could cause angiogenesis, 36 neuronal plasticity, or influence synaptic conduction. 37 Neonatal rodent OECs release nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) into culture media 38 but adult rodent OECs release negligible quantities of BNDF into culture media. 39 Exogenous NGF and BDNF have been shown to enhance glutamatergic neurotransmission in the brain 40 by both pre-and postsynaptic mechanisms 41 and to induce formation of new synapses.…”
Section: Discussionmentioning
confidence: 99%